Acaricidal properties of essential oils from Moroccan plants against immature ticks of Hyalomma aegyptium (Linnaeus, 1758); an external parasite of the spur-thighed tortoise (Testudo graeca). Issue 7 (3rd October 2018) - Laghzaoui, El-Mustapha; Kasrati, Ayoub; Abbad, Abdelaziz; Leach, David; Spooner-Hart, Robert; El Mouden, El Hassan
ABSTRACT: Hyalomma aegyptium (Linnaeus, 1758) is a hard-tick species of the Ixodidae family with the main adult hosts being Palearctic tortoises of the genus Testudo . In Morocco, it is commonly found infecting Testudo graeca that has a wide geographic distribution and is subject to protection through international illegal trade legislation. This tortoise tick has been reported as an important vector of various human and animal pathogens. Unfortunately, to date, there are no strategies to control this hematophagous ectoparasite. The present study was conducted in laboratory to evaluate the acaricidal activity of essential oils (EOs) extracted from six plants of Moroccan origin as an alternative against H. aegyptium . All EOs tested displayed toxic effects on different life stages of H. aegyptium. Mentha suaveolens subsp. timija (LC50  = 0.910 µL/mL and LC90  = 1.465 µL/mL) and Satureja calamintha EOs (LC50  = 0.927 µL/mL and LC90  = 1.347 µL/mL) exhibited higher activity against hatching eggs, whereas Chenopodium ambrosioides EO was comparatively more toxic to larvae (LC50  = 0.444 µL/mL and LC90  = 0.918 µL/mL). Juniperus thurifera var. a fricana (LC50  = 0.0045 mL/cm 2 and LC90  = 0.0118 mL/cm 2 ) and Lavandula pedunculata subsp. atlantica EOs (LC50  = 0.0036 mL/cm 2 and LC90  = 0.0110 mL/cm 2 ) caused high mortality in nymphs. The effect of different EOs is discussed according to their chemical composition and bioactive components.